Life table and demographic parameters of brown planthopper (BPH), Nilaparvata lugens (Homoptera: Delphacidae) on paddy for population studies - Siti Noor Hajjar Md Latip,; Anis Syahirah Abu Bakar, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Brown planthopper (BPH), Nilaparvata lugens (Homoptera: Delphacidae) is one of the most economically important insect pests, by posing a threat to paddy production throughout Asia including Malaysia. Plants turn yellow and dry up rapidly due to infestation. At early infestation, round and yellow patches appear, which soon turn brownish due to the drying up of the plants, known as Hopperburn which is reported to cause yield loss up to 80%. Life table and demographic parameters play important role in determining the key factors that responsible for the highest mortality within population. Therefore, the objective of the study was to construct life table and demographic parameters of BPH. A survivorship and fecundity study of BPH was conducted in laboratory using three cohorts consisted of 108, 112 and 145 one-day old eggs. The survival and mortality of every life stage were observed and recorded daily. Five pairs of one-day old BPH adults were used in fecundity study. The laid eggs were observed daily and longevity of adults were recorded. Standard life table parameters and population age structures were calculated from daily records of survival, mortality and fecundity of each cohort. The highest mortality was recorded in second instar nymph (15.45%) indicated that this stage is the key factor in regulating BPH population. A total of 57.33% individuals have successfully reached at adult stage. The emergence of first female was on day 20 whilst the last female died on day 40. The earliest egg was laid on day 23 and continued until day 40 with maximum oviposition was on day 36 and 37 which constitute 57.73% of total eggs. The intrinsic rate of natural increase (rm) was 0.08 per female per day with mean generation time (Tc) of 32.64 days and doubling time (DT) of 8.19 days. This shows that BPH population has increased and builds up rapidly in short time period. Our results suggested that the control program should be done during early stage of nymph in order to suppress the BPH population effectively. Life table study of BPH on other local rice varieties should be conducted in determining its survivorship and reproduction on other host varieties.